2019
DOI: 10.20525/ijrbs.v8i1.194
|View full text |Cite
|
Sign up to set email alerts
|

The Strategy of Spiritual Leadership

Abstract: To analyze the influence of spiritual leadership on the organizational commitment of lecturers, spiritual leadership on the workplace spirituality, spiritual leadership on spiritual survival, Workplace Spirituality on the organizational commitment of lecturers, and Spiritual Survival towards the organizational commitment of lecturers in  Private Universities in Medan. The study population was all permanent lecturers of private universities owned by  Foundation ( organizations) totaling 425 permanent lecturers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…A set of spiritual leadership principles must be possessed to inspire oneself and others, thereby stimulating a feeling of spiritual survival through membership and abilities. This supported several investigations (Jufrizen et al, 2019;Chen & Yang, 2012;Göçen & Şen, 2021;Hunsaker, 2017;Raddanipour & Siadat, 2013;Sariani, Mahayasa, Maheswari, Astakoni, & Utami, 2022;Anser, Shafique, Usman, Akhtar, & Ali, 2021), which concluded that spiritual leadership has a positive and significant effect on OCB. Therefore, high levels of spiritual leadership lead to an increase in OCB (Helmy, 2016).…”
Section: Path Analysis Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…A set of spiritual leadership principles must be possessed to inspire oneself and others, thereby stimulating a feeling of spiritual survival through membership and abilities. This supported several investigations (Jufrizen et al, 2019;Chen & Yang, 2012;Göçen & Şen, 2021;Hunsaker, 2017;Raddanipour & Siadat, 2013;Sariani, Mahayasa, Maheswari, Astakoni, & Utami, 2022;Anser, Shafique, Usman, Akhtar, & Ali, 2021), which concluded that spiritual leadership has a positive and significant effect on OCB. Therefore, high levels of spiritual leadership lead to an increase in OCB (Helmy, 2016).…”
Section: Path Analysis Resultssupporting
confidence: 87%
“…Previous research by Vondey (2010) concluded that spiritual leaders prioritize morality, sensitivity, mental balance, inner wealth, and ethics while interacting with others. The findings of Jufrizen et al (2019) also concluded that spiritual leadership has a positive and significant effect on OCB. Based on the above explanation, the following hypothesis was proposed: H1: Spiritual Leadership affects Organizational Citizenship Behavior Self-efficacy is the perception of the ability to execute obligations or movements essential to accomplish goals.…”
Section: Introductionmentioning
confidence: 89%
“…Barnett et al, (2005); and Khan et al, (2019) investigated that commitment and environmental protection can be ensured by leaders and employees who act on the phenomenon of spirituality by following their spiritual leaders (Norton et al, 2017;Saleem et al, 2020 ) and Prof. -ecological approach and green creativity. This research also agrees with research (Jufrizen et al, 2019)…”
Section: Tablesupporting
confidence: 93%
“…The research carried out on spiritual leadership and green creativity has a connection with EEC and scholars have also explained the different effects on GC that how employees may be urged to perform creative ideas. Previous research has examined the role of spiritual leadership on employees' environmental commitment at work and within the organization (Jufrizen et al, 2019). Our research is therefore an effort to improve the existing knowledge stream by seeing its role in promoting green creativity through a moderated mediating mechanism.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Spiritual leadership is essential in cultivating a culture that values the spiritual well-being of its followers (Figure 1). Care, concern and respect create a strong relationship between leaders and employees through spiritual leadership [21]. Spiritual activities and goals are closely related to the leader's efficacy in encouraging followers, creating a favourable working atmosphere, increasing trust, and creating positive relationships between employees and leaders to achieve organizational goals [22].…”
Section: -1-spiritual Leadership and Employee Well-beingmentioning
confidence: 99%